FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA APARATUR : STUDI LITERATUR - Ersalina; Afrah Junita; Muhammad Salman (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This article examines in the literature the factors that influence apparatus performance. This research uses data sources obtained through collecting research results from journal articles published on Google Scholar in 2018-2022. The results show that performance can be influenced by self-efficacy, participation in budgeting, information technology utilization, and competence. When an individual has high self-efficacy, is involved in preparing a budget, uses technology, and has appropriate competencies, his performance will increase. From these results it appears that this research has the potential to be reviewed through qualitative or quantitative methods using primary or secondary data. self efficacy, Participation in Budgeting, Utilization of Information Technology, Competence, Performance